2006
DOI: 10.1177/00222194060390050701
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Computer-Assisted Instruction on Number Combination Skill in At-Risk First Graders

Abstract: The purpose of this pilot study was to assess the potential for computer-assisted instruction (CAI) to enhance number combination skill among children with concurrent risk for math disability and reading disability. A secondary purpose was to examine the effects of CAI on spelling. At-risk students were assigned randomly to math or spelling CAI, which they received in 50 sessions over 18 weeks. Acquisition and transfer effects were assessed. The results indicated that math CAI was effective in promoting additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
87
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 39 publications
5
87
0
3
Order By: Relevance
“…math learning | intervention | prediction | multimodal neuroimaging | educational neuroscience M athematical problem solving skills are crucial for academic and professional success (1)(2)(3). Fluency with basic arithmetic provides a foundation upon which more complex skills are built (4)(5)(6). In the past two decades, math-tutoring programs designed to improve basic arithmetic fluency have been developed and tested in classroom and one-to-one tutoring settings (7)(8)(9)(10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…math learning | intervention | prediction | multimodal neuroimaging | educational neuroscience M athematical problem solving skills are crucial for academic and professional success (1)(2)(3). Fluency with basic arithmetic provides a foundation upon which more complex skills are built (4)(5)(6). In the past two decades, math-tutoring programs designed to improve basic arithmetic fluency have been developed and tested in classroom and one-to-one tutoring settings (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Behavioral studies of primary-grade school children by Fuchs and colleagues have shown that the combination of computer-aided intervention and one-to-one tutoring can significantly improve mathematical abilities (6,9). Critically, they found that interventions emphasizing number knowledge and speeded practice with efficient counting strategies can improve math skills in primary-grade school children (9,10,13).…”
mentioning
confidence: 99%
“…In earlier CAI studies (other than NR), positive intervention effects in basic addition have been found in groups of at-risk children with performance below the 25th percentile (e.g., Baroody et al, 2012Baroody et al, , 2013Fuchs et al, 2006). Furthermore, the between-group comparison revealed a significant difference in gain scores of basic arithmetic, favoring the NR group.…”
Section: Discussionmentioning
confidence: 85%
“…As studies have shown individual variation in intervention responsiveness to be large in a group of children with MD (e.g., Dowker & Sigley, 2010;Fuchs et al, 2012;Geary, 2011), we would recommend examining the effects of a tailored, targeted training based on qualified screening assessments. The potential intervention benefits also should be followed by delayed assessments (e.g., Fuchs et al, 2006;Wilson et al 2009). In addition, game log data could provide more detailed information on an individual level, as well as generate insight into how children actually act while using the programs (see Käser et al, 2011 for more on using log file data in analyses of CAI effectiveness).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation